2011
DOI: 10.1016/j.visres.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Vision out of the corner of the eye

Abstract: The margin of the temporal visual field lies more than 90° from the line of sight and is critical for detecting incoming threats and for balance and locomotive control. We show (i) contrast sensitivity beyond 70° is higher for moving stimuli than for stationary, and in the outermost region, only moving stimuli are visible; (ii) sensitivity is highest for motion in directions near the vertical and horizontal axes and is higher for forward than for backward directions; (iii) the former anisotropy arises early in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 48 publications
5
39
0
Order By: Relevance
“…Psychophysics studies have demonstrated that, in humans, the peripheral visual field (up to the edge of vision) is no more sensitive than the central visual field with respect to the discrimination of the direction and speed of motion (van de Grind et al, 1983;McKee and Nakayama, 1984;To et al, 2011b). In our marmoset V1 data (Yu and Rosa, 2014; Fig.…”
Section: Direction Selectivity Is Similar Across the Visual Fieldmentioning
confidence: 60%
“…Psychophysics studies have demonstrated that, in humans, the peripheral visual field (up to the edge of vision) is no more sensitive than the central visual field with respect to the discrimination of the direction and speed of motion (van de Grind et al, 1983;McKee and Nakayama, 1984;To et al, 2011b). In our marmoset V1 data (Yu and Rosa, 2014; Fig.…”
Section: Direction Selectivity Is Similar Across the Visual Fieldmentioning
confidence: 60%
“…In this type of studies, the literature recommendation is to normalize the stimuli to individual threshold units. 30,31 Notably, we also tested the association between global activation measures and diabetic retinopathy grades in this subgroup of patients and we did not find a significant correlation. We assume that gross abnormalities in the HRF in this subgroup could not have driven the main findings of this study.…”
Section: Discussionmentioning
confidence: 83%
“…However, full resolution of visual information is only obtained in the foveal region, covering about 2 degrees of the visual field. Moreover, the periphery is another part of the field of view which is utilized for things like detecting motion and hazards, balance and keeping in lane while driving (Mourant & Rockwell 1970;Holmqvist et al 2011;To et al 2011;Traschütz et al 2012). However, peripheral vision is negatively affected by increases in cognitive load and age.…”
Section: Introductionmentioning
confidence: 99%